Proceedings of SPE Western Regional Meeting 2001
DOI: 10.2523/68844-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transient Dual-Porosity Behavior for Horizontal Wells Draining Heterogeneous Reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIn the literature it has been shown that a bilinear flow regime, characterized by a quarter slope line on the logarithmic derivative diagnostic plot, can arise for horizontal wells draining fractured or layered reservoirs with transient dualporosity behavior during the intermediate linear flow period. In the case of layered reservoirs the bilinear flow is a result of the linear flow in the more permeable layer toward the well and of the linear flow from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several authors 8,9 have demonstrated that in a multilayered reservoir, where a high permeability layer is supported by a tight zone, the pressure response can exhibit a transient dual-porosity behavior. Bilinear flow exists in a horizontal well when it is positioned in a high permeability layer overlying (or underlying) a relatively low permeability layer, resulting in two linear flows: a linear horizontal flow in the most permeable zone and linear vertical flow in the tight zone ( Figure 6).…”
Section: Bilinear Flow (Well A)mentioning
confidence: 99%
“…Several authors 8,9 have demonstrated that in a multilayered reservoir, where a high permeability layer is supported by a tight zone, the pressure response can exhibit a transient dual-porosity behavior. Bilinear flow exists in a horizontal well when it is positioned in a high permeability layer overlying (or underlying) a relatively low permeability layer, resulting in two linear flows: a linear horizontal flow in the most permeable zone and linear vertical flow in the tight zone ( Figure 6).…”
Section: Bilinear Flow (Well A)mentioning
confidence: 99%
“…If the dual-porosity transition occurs when the linear flow regime is the dominant flow regime and for some values of storativity ratio, the pressure derivative of the transient pressure response exhibits an intermediate line of quarter slope. [17][18][19][20] …”
Section: Introductionmentioning
confidence: 99%